2021
DOI: 10.24191/ajue.v17i2.13401
|View full text |Cite
|
Sign up to set email alerts
|

Lecturers’ Organizational Citizenship Behaviours During COVID-19 Pandemic

Abstract: A limited number of studies indicate that organizational citizenship behaviour (OCB) have the potential to contribute to organizational and individual performance. Educators who have positive behaviours such as helping behaviour can help facilitate the learning process. With the spread of COVID-19 pandemic which has led to the growth of online learning, OCBs among educators is needed in facilitating  students’ learning process. This study was conducted to examine the practice of OCB among lecturers from an ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Consequently, understanding why employees engage in OCB is both necessary and insightful. Educators have positive perceptions of organizational citizenship, with behaviors including suggesting improvements for the university, voluntarily assisting new lecturers, and dedicating their personal time to enhance the performance of their students and the university ( Khalid et al, 2021 ; Bastian and Widodo, 2022 ).…”
Section: The Definition Of Ocb and Cwbmentioning
confidence: 99%
“…Consequently, understanding why employees engage in OCB is both necessary and insightful. Educators have positive perceptions of organizational citizenship, with behaviors including suggesting improvements for the university, voluntarily assisting new lecturers, and dedicating their personal time to enhance the performance of their students and the university ( Khalid et al, 2021 ; Bastian and Widodo, 2022 ).…”
Section: The Definition Of Ocb and Cwbmentioning
confidence: 99%
“…When employees engage in Organisational Citizenship Behaviour (OCB), it increases the likelihood of their work group demonstrating superior execution, which in turn improves the overall viability of the organization (Kernodle & Noble, 2013; Schnake & Dumler, 2003). Khalid et al (2021) found that students observed significant levels of organizational citizenship behaviors (OCB) in their teachers during the COVID-19 pandemic, particularly regarding their assistance in adapting to online learning platforms.…”
Section: Introductionmentioning
confidence: 99%
“…When individuals in the organization demonstrate OCB, the group with whom they work has a greater chance of demonstrating superior execution, resulting in improved organizational viability (Kernodle & Noble, 2013;Schnake & Dumler, 2003). During the COVID 19 pandemic, Khalid et al (2021) reported students identified high levels of OCB behaviours in their teachers as they supported the transition to online learning platforms.…”
Section: Introductionmentioning
confidence: 99%